Anti-Inflammatory Effects of Formononetin 7-O-phosphate, a Novel Biorenovation Product, on LPS-Stimulated RAW 264.7 Macrophage Cells - Kim, Min-Seon; Park, Jin-Soo; Chung, You Chul; Jang, Sungchan; Hyun, Chang-Gu; Kim, Seung-Young (MDPI, 2019)
Biorenovation is a microbial enzyme-catalyzed structural modification of organic compounds with the potential benefits of reduced toxicity and improved biological properties relative to their precursor compounds. In this study, we synthesized a novel compound verified as formononetin 7-O-phosphate (FMP) from formononetin (FM) using microbial biotransformation. We further compared the anti-inflammatory properties of FMP to FM in lipopolysaccharide (LPS)-treated RAW264.7 macrophage cells. We observed that cell viabilities and inhibitory effects on LPS-induced nitric oxide (NO) production were greater in FMP-treated RAW 264.7 cells than in their FM-treated counterparts. In addition, FMP treatment suppressed the production of proinflammatory cytokines such as prostaglandin-E-2 (PGE(2)), interleukin-6 (IL-6), and interleukin-1 beta (IL-1 beta) in a dose-dependent manner and concomitantly decreased the mRNA expression of inducible NO synthase (iNOS) and cyclooxygenase-2 (COX-2). We also found that FMP exerted its anti-inflammatory effects through the downregulation of the extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), and nuclear factor kappa B (NF-kappa B) signaling pathways. In conclusion, we generated a novel anti-inflammatory compound using biorenovation and demonstrated its efficacy in cell-based in vitro assays.
Keywords: KAPPA-B ACTIVATION; NITRIC-OXIDE; INDUCED INOS; SIGNALING PATHWAYS; INHIBITION; EXPRESSION; PHOSPHORYLATION; INFLAMMATION; COMPOUND; VITRO